Mitos gregos : o teor sagrado das Hídrias de Dora Ferreira da Silva - Rocha, Priscilla da Silva (2009)
The purpose of the present work is to investigate a part of the mythical imaginary of the poet and translator from São Paulo Dora Ferreira da Silva (1918 2006). It will be done from the analysis of poems which were chosen from the book Hídrias (2004) and from some this author‟s other books. The themes of the poems which were chosen are the Greek mythology and its characters, whose stories are retold in a lyrical way by the writer. Dora Ferreira da Silva brings back the meaning of sacrality that the mythical tradition carries with itself, she also demonstrates as the man is not, definitely, a being which is formed only by the rational thought, but, otherwise, he is extremely subjective and symbolic and goes through, necessarily, the imaginary ways to constitute himself as a complete being. The theory of the imaginary, by Gilbert Durand, that values the human subjectivity and its imaginative aspect was used as a theoretical base for this work and shows how the man will be always incomplete if he does not carry with himself images, symbols, archetypes and myths, themes which are also studied by Carl Gustav Jung and Mircea Eliade, in whose fountains Durand drank and who have part of their works used as theoretical base of this study as well. The myth of Persephone is recurrent in all Dora Ferreira da Silva‟s work and she chose it as her favorite. Through the analysis of poems which have this goddess as the main character, we also investigate in this work, observing the distance between biography and fiction, the relationship that there was between the Persephone and the poet.